2017
DOI: 10.6001/energetika.v63i3.3559
|View full text |Cite
|
Sign up to set email alerts
|

Advanced exergetic analysis of a heat pump providing space heating in built environment

Abstract: In addition to conventional exergy-based methods, advanced exergetic analyses consider the interactions among components of the energy-conversion system and the real potential for improving each system component.The paper demonstrates the results of application of a detailed advanced exergetic analysis to a wastewater source heat pump providing space heating in the built environment. In order to determine thermodynamic parameters of the refrigeration vapour compression cycle in different operating modes, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…This means that the exergy destruction within this component can be reduced through changes in the remaining components (evaporator, condenser and compressor) or in the structure of the overall system. This conclusion completely coincides with the data provided in [3,12,13]. According to the results presented in Fig.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…This means that the exergy destruction within this component can be reduced through changes in the remaining components (evaporator, condenser and compressor) or in the structure of the overall system. This conclusion completely coincides with the data provided in [3,12,13]. According to the results presented in Fig.…”
supporting
confidence: 92%
“…The avoidable parts of exogenous exergy destruction within the evaporator and the throttling valve and caused by compressor are also negative and equal respectively to -13 kWh and -16 kWh. The similar information concerning negative values of exogenous exergy destruction is obtained in a series of works: [3] for a vapour-compression refrigeration machine with R407C, [10] for an absorption refrigeration machine, [13] for a water source heat pump providing space heating, [23,24] for geothermal district heating systems, [25] for a combined cycle power plant. Negative values of exogenous exergy destruction provides negative values of costs and environmental impact due to exergy destruction.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…The relationship between Avoidable and Unavoidable Irreversibility for each stream, Wang et al [22], Sert and Balkan [23], Voloshchuk [54].…”
Section: Definition Equationmentioning
confidence: 99%
“…After improvement, the system exergy loss was decreased by 30.2%, and the exergy efficiency was increased from 6.9% to 9.5%. Voloshchuk [6] found that 63% and 20% of the avoidable endogenous exergy loss came from the inefficient work of the evaporator and condenser by using advanced exergy ways. An advanced exergy study model of the new ASHP is constructed in this article, and the avoidable exergy loss and exergy efficiency of the components and system are studied.…”
Section: Introductionmentioning
confidence: 99%